F, Tasya Hubungan Kemandirian Belajar, Fasilitas Belajar Dengan Hasil Belajar Matematika Siswa Kelas VIII SMPN 2 Palangka Raya - Nahan, Tasya Florensia; Aritonang, Henry; Mairing, Jackson Pasini (FKIP Universitas Palangka Raya, 2024)
This research against the background of mathematics learning outcomes of students who are still relatively low, lack of learning independence, and mathematical learning facilities that are still not optimally used. This study aims to determine the correlation between learning independence and learning facilities with the learning outcomes of Mathematics for Class 8th grade students of SMPN 2 Palangka Raya. The approach used in this research is the quantitative approach with the correlational research type. This research was conducted in the even semester of the academic year 2022/2023. The population in this study were students of class 8th grade SMPN 2 Palangka Raya in the academic year 2022/2023 with the total of population are 352 students and the research samples of 196 students. The results of this study are: (1) there is a significant positive correlation between learning independence and mathematical learning outcomes with very low correlation criteria ( ); (2) there is no significant positive correlation between learning facilities and mathematics learning outcomes ( ); (3) There is a significant positive correlation between learning independence and learning facilities with mathematical learning outcomes with low correlation criteria (0,22767).